Services integration monitor for collaborative workflow management - Pudhota, Leo; Tierney, Andrew; Chang, Elizabeth (IEEE, 2005)
Collaborative workflow management systems in logistic companies require strong information systems and computer network support. These IT integration requirements have expanded considerably with the advent of e-business; utilizing web services and Partner to Partner ecommerce. This paper deals with change management of collaborative workflow in such consortia and proposes architecture for synchronization and monitoring of these services where existing workflow systems are adapted to the changes requested by management. This paper describes conceptual framework of the services monitor which is used to monitor and edit changes resulting in new collaborative workflows.